Preparation of active 3D film patches via aligned fiber electrohydrodynamic (EHD) printing - Wang, Jun-Chuan; Zheng, Hongxia; Chang, Ming-Wei; Ahmad, Zeeshan; Li, Jing-Song (Scientific reports, 2017)
The design, preparation and application of three-dimensional (3D) printed structures have gained appreciable interest in recent times, particularly for drug dosage development. In this study, the electrohydrodynamic (EHD) printing technique was developed to fabricate aligned-fiber antibiotic (tetracycline hydrochloride, TE-HCL) patches using polycaprolactone (PCL), polyvinyl pyrrolidone (PVP) and their composite system (PVP-PCL). Drug loaded 3D patches possessed perfectly aligned fibers giving rise to fibrous strut orientation, variable inter-strut pore size and controlled film width ( via layering). The effect of operating parameters on fiber deposition and alignment were explored, and the impact of the film structure, composition and drug loading was evaluated. FTIR demonstrated successful TE-HCL encapsulation in aligned fibers. Patches prepared using PVP and TE-HCL displayed enhanced hydrophobicity. Tensile tests exhibited changes to mechanical properties arising from additive effects. Release of antibiotic from PCL-PVP dosage forms was shown over 5 days and was slower compared to pure PCL or PVP. The printed patch void size also influenced antibiotic release behavior. The EHDA printing technique provides an exciting opportunity to tailor dosage forms in a single-step with minimal excipients and operations. These developments are crucial to meet demands where dosage forms cannot be manufactured rapidly or when a personalized approach is required.